El dinamismo de lo social y personal en Filosofía de la Realidad Histórica: Relectura desde la antropología ellacuriana - Martínez Vásquez, Luis Arturo (2022)
Ellacuría’s anthropology continues Zubirian work; in which the dynamisms of reality constitute a metaphysical unit. In Filosofía de la realidad histórica, the dynamism of biological life allows the involvement of social and the personal components, with a biological and chronological priority of the social.